Meningkatkan Kemampuan Membaca Permulaan Melalui Video Interaktif Pada Anak Disabilitas Rungu - Delvi Maria Damanik; Damri Damri; Mega Iswari; Johandri Taufan (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
This study aims to improve early reading skills through the use of interactive videos for children with hearing impairments. The research employed a Classroom Action Research (CAR) design conducted in Grade II at SLB Negeri Simalungun. The research subjects consisted of two students with hearing impairments, identified by the initials AD and VN. Based on the initial assessment, both students’ early reading abilities were categorized as low, with achievement percentages of 30% for AD and 30% for VN. The study was implemented in two cycles, each comprising the stages of planning, action implementation, observation, and reflection. The results of Cycle I indicated an improvement in early reading skills, with AD achieving 50% and VN achieving 50%. Furthermore, in Cycle II, students’ early reading abilities increased significantly, with achievement percentages reaching 80% for AD and 80% for VN. Data were collected through observation using an early reading skills assessment sheet, while data analysis was conducted using descriptive quantitative techniques by comparing achievement results across cycles. The findings demonstrate that the use of interactive videos is effective in enhancing early reading skills among children with hearing impairments. These results confirm that interactive, visually based learning media aligned with the learning characteristics of children with hearing impairments can effectively improve students’ attention, comprehension, and overall learning outcomes.